High coercivity α-Fe2O3 nanoparticles prepared by continuous spray pyrolysis. Issue 65 (16th July 2015) - Kant, Rich; Kumar, Dinesh; Dutta, Viresh
<x xml:space="preserve">Abstract</x> Surfactant free growth of high coercivity (HC) α-Fe2O3 nanoparticles by continuous spray pyrolysis (CoSP).